Cochlear Implant Performance in Adult Patients with Absent Intraoperative Electrically Evoked Compound Action Potentials. (3rd March 2020) - Cooper, Timothy; Melder, Katie L.; Hyre, Rick; Hobson, Candace E.; McCall, Andrew A.; Hirsch, Barry E.
Abstract : Objective: To describe cochlear implant performance outcomes in adult patients in whom no intraoperative electrically evoked compound action potential (ECAP) responses were able to be obtained despite intracochlear electrode placement. Study Design: Retrospective case review. Setting: Academic tertiary center. Subjects and Methods: Patients 18 years of age and older undergoing cochlear implantation between May 2010 and September 2018 with absent ECAP measurements intraoperatively with intracochlear electrode positioning were identified. Patient performance on sentence recognition testing using the Hearing in Noise Test (HINT) and AzBio at 6 to 12 months postoperatively was compared to preimplantation scores. Additional collected data included patient demographics, etiology of hearing loss, and preoperative pure‐tone average (PTA) and word recognition scores (WRSs). Results: Intraoperative ECAP measurements were unable to be obtained in 15 cochlear implants performed on 14 patients out of 383 cochlear implant cases. Of the patients with absent ECAP measures, the mean ± SD age was 61.7 ± 15.7 years. Causes of hearing loss included congenital hearing loss, meningitis, autoimmune inner ear disease, otosclerosis, presbycusis, and Ménière's disease. The average preoperative PTA was 103.5 ± 17.0 dB. Twelve implanted ears had a WRS of 0% and 9 had a HINT score of 0% prior to surgery. The mean HINT score at 6 to 12 months postimplantation was 57.8% ± 37.8% and had improved by 42.6% ± 35.6% compared to the mean preimplantation HINT score (95% confidence interval, 22.0%‐63.1%, P =. 001, paired Student t test). Conclusion: There is a wide range of cochlear implant performance in patients with absent intraoperative ECAP measures ranging from sound awareness to HINT scores of 100%.